2010
DOI: 10.1136/jech.2009.090720
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the onset of non-specific neck pain: a systematic review

Abstract: Various clinical and sociodemographic risk factors were identified that have implications for occupational health and health policy. However, there was a lack of good-quality research investigating the predictive nature of many other variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
142
2
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(162 citation statements)
references
References 58 publications
8
142
2
10
Order By: Relevance
“…These multivariate analyses (Table 6) showed that older age was associated with neck/ shoulder pain for both genders in our study, in agreement with a recent literature review 31) . We found that older age was a protective factor for back pain among men in our study.…”
Section: Comparison With Literaturesupporting
confidence: 93%
See 1 more Smart Citation
“…These multivariate analyses (Table 6) showed that older age was associated with neck/ shoulder pain for both genders in our study, in agreement with a recent literature review 31) . We found that older age was a protective factor for back pain among men in our study.…”
Section: Comparison With Literaturesupporting
confidence: 93%
“…The prevalence of musculoskeletal symptoms differed between men and women, as neck/shoulder and upper extremity pain were more prevalent among women than men, and this was the reverse for back and lower extremity pain in this population of vineyard workers. Differences in musculoskeletal symptoms were reported between men and women in the literature; in particular, the female gender was found to be a risk factor of neck pain 31) . Strong gender differences were also observed regarding occupational exposures, for both biomechanical and psychosocial work factors, in our study, confirming that even in the same occupation, men and women do not have the same working conditions 28) .…”
Section: Comparison With Literaturementioning
confidence: 99%
“…Patients with MS have disturbances in the neck region and are exposed to kyphoscoliosis due to the muscular imbalance, resulting in a severe pressure on nerves (19). Also, neck pain in patients with MS is more than the pain in the trunk and back (20).…”
Section: Introductionmentioning
confidence: 99%
“…Neck pain is defined as discomfort or dull pain caused by muscle stiffness around the back of the head and through the shoulder and/or scapular region [11]. Again, in many cases, chronic neck pain is non-specific [12]. Neck pain can be aggravated by a number of factors, including: cervical spine disease, glenohumeral joint disease, cardiovascular disease, eye fatigue, and temporomandibular arthrosis [13] [14].…”
Section: Introductionmentioning
confidence: 99%